Pengaruh Corporate Social Responsibility, Ukuran Perusahaan, Dan Profitabilitas Terhadap Nilai Perusahaan - Bisri, Ahmad Alif Hayyumil; Amirya, Mirna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the effect of Corporate social responsibility or CSR, company size, and profitability on the value of mining companies listed on the Indonesia Stock Exchange in 2019-2020. This study used data from 27 mining companies listed on the Indonesia Stock Exchange for the 2019-2020 period which was determined using the purposive sampling method that can be aplplied by data collection techniques using the archival method which was carried out by collecting financial reports and CSR disclosure reports from each sample company. Furthermore, the data analysis techniques used are descriptive statistical analysis, classical assumption testing, and multiple linear regression. This research supports signalling theory. Furthermore, this study shows that the independent variables in this study consisting of corporate social responsibility, company size, and profitability have a positive and significant effect to the dependent variable, namely the value of the company. This, with this research, researcher want to give recommendations for companies to pay more attention to aspects of corporate social responsibility, company size, and profitability that have an influence on the value of the company as well as the decision of investors in determining investments.